SIMULASI INVESTASI SAHAM BERBASIS WEB PADA PT. PHILIP SECURITIES INDONESIA - Lailyn Puad; Pratama Hendri Wibowo (JURNAL AKADEMIKA)
Information technology devices become a requirement which is used to improve the performance of a system to encourage every company seeks to build a system that can facilitate its performance and improve its service to the general public. Thesis of this paper describes the stages of the building an Investment Simulation System Web-Based Shares in PT. Phillip Securities Indonesia to facilitate the PT. Phillip Securities Indonesia in providing information on the procedure how to invest in stocks to provide security for the company investors before investing in the stock significantly. This information system is built using Adobe Dreamweaver CS5 and MySQL database relating to research obtained through field studies and literature